School in the hospital, the key role of an educating community - Marilena Di Padova; Massimo Pettoello-Mantovani; Anna Dipace (Elsevier, 2024)
Ensuring a stable routine is crucial for every child, particularly during their hospitalization. Children facing illness undergo treatments that often require strict care routines, involving invasive medical procedures, lengthy hospital stays, and separation from familiar environments like home or school. These prolonged hospitalizations disrupt their usual schedules, resulting in feelings of isolation from family and friends for extended and uncertain periods. These difficulties may impede medical treatments and could contribute to psychological distress, further impacting the well-being of both the patient and their family.Community education distributes its educational role among all those stakeholders who collaborate to promote an equitable and inclusive learning environment. While the school typically serves as the primary educational institution, for hospitalized children, their educational experience may differ significantly from that of their peers. Therefore, the hospital school encompasses a diverse team of professionals working collaboratively to deliver a tailored educational experience. This article emphasizes the critical importance of expanding such programs within hospital environments. It highlights the necessity of developing robust educational frameworks capable of adapting to the diverse needs and evolving structures of healthcare systems. Finally, the article emphasizes the imperative of upholding high-quality education, ensuring the right to education for all, and honoring the principles of special educational needs as outlined in the 1994 UNESCO Salamanca Statement